Individualization and the Delivery of Welfare Services - Yeatman, A. author. aut Link
XIV, 279 p.
Keywords: The conception of welfare services has changed to consider the more specialized needs of individual users or consumers. This book examines the contradictions and complexities of contemporary individualized welfare services, with special reference to service groups who are deeply dependent on service delivery for their quality of life.